2009
DOI: 10.1177/0022185608101709
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact of Industrial Strikes: Does Involvement in Union Activity during Strikes make a Difference?

Abstract: The current study investigated the psychological impact of a United Steelworkers of America strike on the steelworkers involved, and the relationship between psychological well-being and individuals' levels of involvement in union activity during the strike. Three hundred and fifty-one steelworkers (302 'strikers' and 49 'non-strikers') completed surveys measuring a range of demographic and psychological well-being variables. Strikers, compared to non-strikers, reported higher levels of depression, anxiety, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…The most frequently needed support mechanism is institutional daycare centers. Supports provided by organizations for child care of working mothers to work-family balance are daycare centers in the workplace (Beauregard & Henry, 2009;Glass & Riley, 1998;Meurs, Breaux, & Perrewe, 2008;Veiga, Baldridge, & Eddleston, 2004), affordable access to contractual daycare centers (Fowler, Gudmundsson, & Whicker, 2006), providing financial support for childcare costs (Beauregard & Henry, 2009;Glass & Riley, 1998) and providing lactation rooms (Çakmak-Otluoğlu, 2015, p.85). Similarly, research by Albrecht (2003) showed that the support mechanisms called "family-friendly workplace policies" do not adequately support working mothers.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The most frequently needed support mechanism is institutional daycare centers. Supports provided by organizations for child care of working mothers to work-family balance are daycare centers in the workplace (Beauregard & Henry, 2009;Glass & Riley, 1998;Meurs, Breaux, & Perrewe, 2008;Veiga, Baldridge, & Eddleston, 2004), affordable access to contractual daycare centers (Fowler, Gudmundsson, & Whicker, 2006), providing financial support for childcare costs (Beauregard & Henry, 2009;Glass & Riley, 1998) and providing lactation rooms (Çakmak-Otluoğlu, 2015, p.85). Similarly, research by Albrecht (2003) showed that the support mechanisms called "family-friendly workplace policies" do not adequately support working mothers.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Studies of job action in the postal industry, for instance, have indicated that in the case of public sector labour disputes, workers’ feelings towards the government became more negative as a consequence of the nature of the state’s involvement in the strike (Langford, 1996). More recent literature suggests that social factors can be attributed to the continuation of stress among employees even after a strike has been settled (Fowler et al, 2009), part of the ‘dark side of solidarity’ (Thommes et al, 2014). Our article bridges these aspects of existing research by joining political economy with social scientific lines of enquiry examining what prompts workers to engage in job action in the context of legislative intervention and a legacy of corporate restructuring.…”
Section: ‘Permanent Exceptionalism’ and Labour Militancymentioning
confidence: 99%
“…One means of achieving this mandate is through collective bargaining with the employer. When there is a breakdown in the collective bargaining process, the resulting strikes or lockouts are a significant source of stress for management, employees, and their families (Barling & Milligan, 1987;Bluen & Barling, 1988;Fowler, Gudmundsson, & Whicker, 2009;MacBride, Lancee, & Freeman, 1981;Vispo & Shine, 1985). Members of management may face longer workdays as they perform the duties of striking or locked-out employees, or they may encounter altercations as they cross picket lines.…”
Section: Résumémentioning
confidence: 99%